Caracterização genética populacional e parentesco em Tapicuru, Plegadis chihi (Vieillot, 1817) (Threskiornithidae), do Rio Grande do Sul - Souza, Andiara Silos Moraes de Castro e (2011)
The white-faced ibis, Plegadis chihi (Vieillot, 1817) (Pelecaniformes, Threskiornithidae) is a migratory waterbird that breeds in colonies in the southern of Brazil. In point of view of genetics, this species was not studied. In this study we genetically characterized two populations from Rio Grande do Sul, and we classified nestlings sampled inside the same nests in one category of relatedness (full-siblings, half-siblings or unrelated). We extracted DNA from 247 nestlings (either from growing feathers or muscle tissue) and amplified it by PCR. We screened 44 microsatellite heterologous loci developed for species belonging to: Threskiornithidae, Ciconiidae and Ardeidae families. Individuals were genotyped at successfully amplified loci, and six loci proved to be polymorphic. The number of alleles per locus ranged from two (NnNF5) to 10 (Aaju3), and average expected and observed heterozygosities were 0.572 and 0.552, respectively. NnNF5 and Eru6 were excluded from the analysis of genetic structure since they are in linkage disequilibrium with Eru5 and Eru4, respectively. The AMOVA analysis showed that most of the genetic diversity is distributed within populations, and not between populations. The FST value, although small, was significant (0.009, p = 0.05), indicating that there is low differentiation between colonies studied. The results suggest that populations are structured and that little gene flow occurs between them. The ratio between males and females in our samples was not different from the expected 1:1. One hundred and six pairs of nestlings taken from the same nests, using Aaju3, Eru2, Eru4, Eru5 e Eru6 loci, were inspected for relatedness. Our analytical procedure allowed us to identify the kinship of 55% of the pairs. Among the classified pairs of nestlings we found: 62% of fullsiblings, 5% of half-siblings and 33% of unrelated nestlings. Relatedness categories found between pairs of nestlings are showing that genetic monogamy is not the only mating system, but extra-pair fertilization and brood parasitism can be occurring.